Improvement of fill factor by the utilization of Zn-doped PEDOT:PSS hole-transport layers for p-i-n planar type of perovskite solar cells - Alishah, Hamed Moeini; Choi, Fatma Pinar Gokdemir; Kuruoglu, Furkan; Erol, Ayse; Gunes, Serap (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Poly (3,4-ethylenedioxythiophene)-poly (styrene sulfonate (PEDOT:PSS) is a widely-known conductive polymer mixture that is mostly engaged as a hole transport layer (HTL) in organic and perovskite so-lar cells (PSCs). In this study, it has been demonstrated that the use of Zn as an additive in PEDOT:PSS solution improved the photovoltaic performance of the ambient air solution-based fabrication of methy-lammonium lead tri-iodide (MAPbI(3)) based devices. The short circuit current density (JSC) of the device increased from 15.4 to 17.2 mA/cm(2), while the fill factor (FF) improved from 0.70 to 0.83 by using Zn-doped PEDOT:PSS as a hole transport layer (HTL), which is a record value for only gamma-butyrolactone (GBL) based MAPbI(3) PSCs. Additionally, open-circuit (VOC) value is boosted up from 890 to 925 mV by Zn-doping, which might be linked to the increased work function of the investigated HTLs. Moreover, the synergetic effect of improved electrical conductivity and hole mobility of PEDOT:PSS film and decreased the trap density of perovskite led to an increase of 37% in power conversion efficiency (PCE) and the stability of the inverted planar PSCs. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: PEDOT:PSS; Zn doping; Inverted; MAPBI(3); Perovskite; PERFORMANCE; EFFICIENT; CONDUCTIVITY; HYSTERESIS; RECOMBINATION; SOLVENT; CARBON; Electrochemistry